DIGITALIZATION, DIGITAL GOVERNANCE AND DATA-DRIVEN DECISION MAKING: AN INEVITABLE COMBINATION AND CONTRIBUTION TO REPRESENTATIVE DEMOCRACIES, CRITICAL ANALYSIS AND DISCUSSION - Muhammad Noaman Yousaf; Nadia Noureen; Kainat Zafar; Mahak Fatima Durrani (International Journal of Contemporary Issues in Social Sciences, 2024)
Digitalization is concerned as an indispensable part of modern-day politics and representative democracies. More and more countries are getting their governance structures digitalized for effective and efficient governance. Data driven decision making is playing a predominant role across the globe as it has significantly ameliorated the daunting task of governance for states and governments. Digitalization in politics and governance has both received acclamation as well as criticism as the advocates and critics both hold their valid arguments concerning their consequences for representative democracies. In the developed world Europe and Americas, the rise in the trend has captivated and attracted the attention of scholars and policy makers arguing on its future potential and challenges for representative democracies. With arguments and criticism on both ends one thing is clear that digitalization in modern democracies is an inevitable fact and necessary inclusion into politics and governance process. With all of its pitfalls concerned, the reforms are to be brought in the digital structure on both technical and ethical lines and it does not suggest indirectly the denouncement of the structure in any way. The article is an effort to analyze and discuss the effects of digitalization on governance and decision making in Europe, America and Australian continent taking case studies of countries.